RELEVANSI METODE PEMBENTUKAN PENDIDIKAN KARAKTER DALAM KITAB TA’LIM AL-MUTA’ALLIM TERHADAP DUNIA PENDIDIKAN MODERN (Program Studi Pendidikan Agama Islam, 2016)
THE RELEVANCE OF CHARACTER EDUCATION ESTABLISHMENT METHOD IN TA’LIM MUTA’ALIM BOOK TOWARDS MODERN EDUCATION WORLD. Character education in ta’limul-muta’aalim (the method of learning) by Burhanuddin al-Zarnuji is an internalization process of character and ethic into a student. This process covers mental development based on the faith concept. The failure of character education is because of the lack of the faith and the ethic. Consequently, the character development is obstructed and even it is failed. To create character and ethic learners, Islamic education should point the aim of education on individual development who knows the position, to the God, to the society, and to themselves. Ta’limul-muta’allim formulated three important methods in character development covering body and soul, i.e., ilqa’ al-nasihah (advisory) and affection method; Mudzakarah, Munadharah, and Mutharahah method; and mental and spiritual development method. These three methods are needed to check the relevance to current education. This library research showed that these method are still relevance to use in nowadays education.